2019
DOI: 10.7759/cureus.5700
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nerve Block in Lymphedema Treatment: A Systematic Review

Abstract: Although the sympathetic nerve system has been described as a modulator of lymphatic circulation, it has not been targeted in the treatment of lymphedema. We conducted a systematic review of publications assessing the use of sympathetic nerve block in lymphedema treatment. We hypothesized that sympathetic nerve block may be a promising treatment option for lymphedema patients. We conducted a comprehensive systematic review of the published literature on the use of sympathetic nerve block in lymphedema treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regarding the effect of thoracic sympathectomy on BCRL of the upper arm, more patients improved in Group TS compared to Group Sham—8 of 11 patients showed decreased lymphedema in Group TS compared with 2 of 10 cases in Group Sham. Studies on BCRL revealed improved outcome; however, these studies recruited small samples and were not controlled 40,41 . Park et al 42 compared the effects of a stellate ganglion block with complex decongestive therapy in 38 patients with BCRL, and they pointed out that both sympathetic block and complex decongestive therapy decreased limb circumference without a statistically significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of thoracic sympathectomy on BCRL of the upper arm, more patients improved in Group TS compared to Group Sham—8 of 11 patients showed decreased lymphedema in Group TS compared with 2 of 10 cases in Group Sham. Studies on BCRL revealed improved outcome; however, these studies recruited small samples and were not controlled 40,41 . Park et al 42 compared the effects of a stellate ganglion block with complex decongestive therapy in 38 patients with BCRL, and they pointed out that both sympathetic block and complex decongestive therapy decreased limb circumference without a statistically significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] A systematic review that included case reports, retrospective studies, and RCTs, assessed the effect of sympathetic nerve blocks in lymphedema in a sum of 187 subjects and noted that sympathetic blocks reduced lymphedema—shown by reduced limb circumference—and also improved patient-reported outcomes like pain. [ 52 ] A randomized trial compared SGB and CDT in 38 patients with BCRL and found both treatment modalities to be effective in reducing the swelling, and there were no significant differences among the groups. Hence, SGB can be considered as an alternative treatment modality for BCRL.…”
Section: Reviewmentioning
confidence: 99%
“…The first-line treatment for lymphedema patients is conservative therapy, but surgical therapies are considered if outcomes are not optimal. Our team have been studying the efficacy of multiple surgical procedures that may be used for treatment of lymphedema (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Between them, vascularized lymph node transfer (VLNT) is a physiologic surgical therapy that consists of removing lymph node tissues from a donor site and transferring these free flaps to the lymphedematous limb (4,17).…”
Section: Introductionmentioning
confidence: 99%